Factors Influencing System Integrators Adoption Intention of a Wireless Smart Home System in Australia - Trovato, Gianluca; Roach, Scott (ASEAN Journal of Management & Innovation, 2024)
This study focuses on the adoption intentions of wireless home automation systems (WHASs) by systems integrators (SIs) in Australia in the context of business-to-business practices. The research applies the Theory of Planned Behavior, derived from behavioural models, such as Technology Acceptance Model, The Unified Theory of , Acceptance, and Use of Technology and several more recent extentions for exploring the motivations of SIs in adopting WHASs. It uses a mixed-methodology approach, starting withan extensive literature review, for a full identification of factors favourable to the adoption of a WHAS, followed by a series of face-toface interview with SIs, and concluded by an online survey involving 850 SIs operating in Australia. The data thus collected were subjected to statistical analysis to fully explore the dominated by males and small businesses, the online surbey indicated a strong consensus on all the proposed variables: Brand, Product Reliability, Product Interoperability, Product Maintaibility, (dedicated) Contact Point, Seamless Purchase Experience, aftersales Services. Technology Transfer, Cost Support, and Relationship and Cocreation. Qualitative interviews revealed preferences and concerns regarding product features, brand preferences, and services. The statistical analysis confirmed the existence of a linear relationship between the variables and adoption intentions, underlining the significance of brand, technology transfer and the SI and WHAS manufacturer relationship.